PENINGKATAN MUTU PENDIDIKAN MELALUI MANAJEMEN BERBASIS SEKOLAH (MBS) - A.SUHARDI A.SUHARDI (Adaara: Jurnal Manajemen Pendidikan Islam, 2017)
This paper describes improving the quality of education through school-based management, committee involvement and effectiveness of school implementation, curriculum implementation, and learning outcomes in schools. The education stake holders should be able to respond and accommodate the expectations and demands of the community in the decision-making process to improve the quality of education. The process transformation of school-based management should be a major part of the decision-making process in improving the quality of education. While the community is required for the participation in order to better understand education, while the government plays a role in determining the basic framework of education policy.